Vaccination and food consumption: association with Post-Acute COVID-19 Syndrome in Brazilian adults (CUME Study) - Brandão, Marlise Lima; Hermsdorff, Helen Hermana Miranda; Leal, Arieta Carla Gualandi; Bressan, Josefina; Pimenta, Adriano Marçal (Frontiers in Nutrition, 2025)
BackgroundPost-Acute COVID-19 Syndrome (PACS) is an important sequalae of COVID-19. Then, our objective was to analyze the risk and protective factors for PACS in Brazilian adults participating in the Cohort of Universities of Minas Gerais (CUME Study), with emphasis on COVID-19 vaccination and food consumption.MethodsIn this sub-study, we included 2,065 participants of CUME Study who answered the baseline questionnaire in 2016 or 2018 or 2020 or 2022, and the follow-up COVID-19/PACS-specific questionnaire in 2023. PACS diagnosis was based on self-reporting of continuation or development of new symptoms 3 months after the initial SARS-CoV-2 infection, with these symptoms lasting for at least 2 months with no other explanation. To estimate the risk and protective factors for PACS, hierarchical multivariate statistical analysis was conducted using the Cox regression technique, producing two models: (1) focusing on consumption of macro and micronutrients; (2) focusing on consumption of food groups.ResultsAfter a median of 5.5 years of follow-up, 54.4% of the participants reported PACS. When we analyzed the consumption of macro and micronutrients, higher intake of proteins (HR: 1.36; 95% CI: 1.06–1.74-4th quartile) and lipids (HR: 1.23; 95% CI: 1.02–1.48-4th quartile) were risk factors for PACS. On the other hand, higher intake of vitamin C (HR: 0.78; 95% CI: 0.64–0.94-4th quartile), vitamin D (HR: 0.81; 95% CI: 0.67–0.99-4th quartile), and zinc (HR: 0.66; 95% CI: 0.52–0.83-4th quartile) were protective factors for the outcome (model 1). When we analyzed the consumption of food groups, higher intake of eggs (HR: 1.59; 95% CI: 1.34–1.89-4th quartile) increased the risk of PACS, whereas, respectively, higher and intermediate consumption of white meat (HR: 0.84; 95% CI: 0.71–1.00-4th quartile) and vegetables (HR: 0.81; 95% CI: 0.67–0.99-2nd quartile; HR: 0.81; 95% CI: 0.67–0.99-3rd quartile) decreased the risk of the outcome (model 2). In both models, pre-infection COVID-19 vaccination was a protective factor for PACS.ConclusionA healthy diet, with higher consumption of white meat, vegetables and specific micronutrients (vitamin C, vitamin D, zinc), in parallel with pre-infection COVID-19 vaccination, is essential to reduce the risk of PACS.